Women in Indonesian Films about â€œEastern Indonesiaâ€ - Karolus, Meike Lusye (Jurnal Perempuan, 2018)
The purpose of this study is to explain about womenâ€™s positions and roles that are represented in films as agents who frame identity and ethnical stereotype of â€œthe Eastâ€. By using intersectional feminist perspective, the study analyse texts from three Indonesian films which using film sets in the regions of Eastern Indonesia as follows: Aisyah: Let Us Be a Family (2016), Salawaku (2016), and Marlina, the Murderer in Four Acts (2017). Findings show that films about Eastern Indonesia still embed with the perspectives of orientalism and colonialism. Women from non-Eastern Indonesia are commonly represented to having superior positions and important roles in educating and spreading the feeling of nationalism. On the other hand, Eastern Indonesian women are mostly represented inferior and alienated from their communities and nature.Â Â